Inovasi Buku Ajar Berbasis Kurikulum Merdeka Di Sekolah Dasar: Pengembangan dan Implementasi - Nuril Nuzulia; Abd Gafur; Abdul Ghaffar S; Marudin Marudin; Tuti Handayani (SAP (Susunan Artikel Pendidikan), 2025)
The development of a learning planning textbook based on the Independent Curriculum aims to provide practical guidance for educators in designing adaptive and tailored learning processes. The Independent Curriculum prioritizes flexibility, creativity, and student character development, so this textbook is designed to support the understanding and application of these principles. The research and development process was carried out by adapting the Borg and Gall model. Of the ten existing development stages, the researcher only implemented seven stages. The development results show that: 1) the developed module includes a cover, foreword, table of contents, materials, implementation of learning tools, and author biodata. Assessments from material experts reached 82.6% with good qualifications, learning design experts 81.3% with good qualifications, and practitioner experts 81.3% with good qualifications. 2) In terms of textbook appeal, the researcher conducted a post-test on 30 students, with an achievement percentage of 91.6% included in the very good qualification. This indicates that the textbook has met the criteria of being attractive and valid. Data analysis using Paired Samples T Test with SPSS 25, and the results showed a Sig 0.000 < 0.02, so the null hypothesis (Ho) was rejected. This means there is a significant difference in student learning outcomes after using the textbook.